2021
DOI: 10.1038/s41598-021-00767-9
|View full text |Cite|
|
Sign up to set email alerts
|

Listeria monocytogenes sensitivity to antimicrobial treatments depends on cell origin

Abstract: In this study we investigated how cell origin could affect the efficacy of an antimicrobial treatment (mild heating combined with terpenoids) in Listeria monocytogenes Scott A, considering cells from: 1. single colony, 2. glycerol stock, 3. cold adapted culture, and 4. fresh culture in stationary phase. After treatment, culturability on BHI medium and viability assessed by flow cytometry were evaluated. Our results showed that the cell origin significantly impacted viability and culturability of L. monocytogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Based on these results, we hypothesized that EO of R. fruticosus was the only plant derivative able to exert a bactericidal effect, i.e., to induce a relevant increase of dead cells. Indeed, the initial discrepancy between viability and culturability could suggest the occurrence of viable but not culturable cells (VBNC), a great safety concern because of the ability to reverse to a viable status 33 . However, considering both plate counting and flow cytometry analysis, it seems that the increase of culturability (log CFU/ml) and viability (i.e., % of live cells) observed starting from 48 h of incubation was likely due to the multiplication of the few cells survived to the effect of this EO rather than a resuscitation phenomenon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, we hypothesized that EO of R. fruticosus was the only plant derivative able to exert a bactericidal effect, i.e., to induce a relevant increase of dead cells. Indeed, the initial discrepancy between viability and culturability could suggest the occurrence of viable but not culturable cells (VBNC), a great safety concern because of the ability to reverse to a viable status 33 . However, considering both plate counting and flow cytometry analysis, it seems that the increase of culturability (log CFU/ml) and viability (i.e., % of live cells) observed starting from 48 h of incubation was likely due to the multiplication of the few cells survived to the effect of this EO rather than a resuscitation phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…The growth dynamics in the presence of sub-lethal concentrations of plant derivatives were modeled to highlight differences in the cell kinetics. Finally, L. monocytogenes cells cultivated in the presence of such plant derivates were analysed according to a flow cytometric protocol 32 , 33 , to better evidence their effect on cell viability and culturability.…”
mentioning
confidence: 99%
“…Interestingly, a recent study found that the mild heat treatment when combined with thymol and carvacrol caused a partial or total inactivation of Listeria monocytogenes , mainly affecting cell culturability rather than viability. The culturability of the cells was also less affected when the inoculum derived from a single colony, indicating the importance of the physiological state of the cells that are used in an antimicrobial assay [ 32 ]. The discrepancy between the culturability and viability that was observed in the present study highlighted the overestimation of the treatment success if considering the classical plate counting.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the recent progress in elucidating the synergistic activity of EOs and mild heat treatment [ 7 , 13 , 16 , 17 , 25 , 26 , 27 , 28 , 29 , 30 ], little is known about the effect of antimicrobial-assisted pasteurization of fruit juice on food pathogen viability [ 21 , 31 , 32 ]. It is well known that the use of traditional, culture-based microbiological approaches can lead to an overestimation of treatment efficacy [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the impact of EOs and PEs on E. faecalis FC12 viability, an FCM protocol (38,58) was used, and the data obtained after 0, 24, 48, and 72 h of incubation at 20 • C were compared with those derived from plate counting. In particular, the total cell number, expressed as a log of cells stained with SYBR-Green I independently of their physiological state, was compared with cell culturability, expressed as log CFU/ml as predicted by the models (Figure 4A).…”
Section: E Ect Of Plant Derivatives On Cell Viability and Culturabilitymentioning
confidence: 99%